More, Better, and More Inclusive Industrial Jobs in Ethiopia : Summary of Evidence Base and Knowledge Gaps - Maaskant, Koen (World Bank, Washington, DC, 2022)
This note aims to shed light on how Ethiopia’s efforts towards export-led industrialization can create more, better, and more inclusive jobs. It first reviews the evidence on how global value chain participation and industrialization have led to improved employment outcomes across the globe, before turning to the evidence on Ethiopia’s industrialization experience so far. Significant progress in building this evidence base has been made in recent years, including more recently through different analytical outputs produced under the World Bank Group’s analytical program on industrial labor, highlighted in this note. However, significant knowledge gaps remain. The note concludes by outlining ideas for a future research agenda on industrial labor in Ethiopia, focusing on key areas for policy-oriented research.